2013
DOI: 10.22495/cocv11i1c7art3
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and firm valuation in emerging markets: evidence from UAE listed companies in the Middle East

Abstract: There has been previous empirical research on corporate governance and board of directors which focused on attempting to find a direct relationship between internal governance variables and firm valuation. It has however also been argued that there are differences in the nature, direction, magnitude and processes of operation of this relationship between developed and developing financial markets because of differences in their respective economic, social, regulatory framework and market behaviour . This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In the model studied, the size of the board of directors and the size of the audit committee were found to not affect firm value, so that H3 dan H5 was rejected. This result is in line with (Adawi & Rwegasira, 2013;Bhat et al, 2018) where changes in the size of the board of directors do not affect firm value. This demonstrates that increasing the number and size of the board of directors and audit committee will not solve the agency problem in the company and will have no impact on the value of the company.…”
Section: Variablesupporting
confidence: 87%
See 1 more Smart Citation
“…In the model studied, the size of the board of directors and the size of the audit committee were found to not affect firm value, so that H3 dan H5 was rejected. This result is in line with (Adawi & Rwegasira, 2013;Bhat et al, 2018) where changes in the size of the board of directors do not affect firm value. This demonstrates that increasing the number and size of the board of directors and audit committee will not solve the agency problem in the company and will have no impact on the value of the company.…”
Section: Variablesupporting
confidence: 87%
“…In a study conducted (Kota & Tomar, 2010;Kumar & Singh, 2013;Mak & Kusnadi, 2005) board size was found to have a negative effect on firm value. Positive results were found in research (Buallay et al, 2017;Lidyah et al, 2019), in addition (Adawi & Rwegasira, 2013;Bhat et al, 2018) revealed that the size of the company's board does not affect firm value. Based on the description above, the third hypothesis developed is as follows: H3 : The size of the board of directors affects the value of the company…”
Section: Board Of Directors On Firm Valuementioning
confidence: 95%
“…(Dimitropoulos and Tsagkanos 2012) says that the quality of corporate governance leads to greater profitability and viability. Many studies have also evaluated the relationship between CG and (i) the overall success of companies (Korent et al 2014), (ii) transparency and financial disclosure (Mallin 2002), (iii) dividend policy (Garay and González 2008), (iv) risk profile/risk disclosure (Elshandidy and Neri 2015), (v) investor protection (Klapper and Love 2004), (vi) firm performance (Aebi et al 2012), (vii) valuation of a company (Adawi and Rwegasira 2013), and (viii) formation of a board-level technology committee (Premuroso and Bhattacharya 2007).…”
Section: Impact Of Corporate Governance Mechanism On Various Factorsmentioning
confidence: 99%
“…Board meetings are significantly and positively associated with company performance Adawi and Rwegasira [28] and Satirenjit, et al [25] specifically test the effects of board meeting on firm accounting performance they concluded that board diligence in terms of board meetings is found to have an adverse effect on firm performance. However contradictory findings Malik and Nehra [29] stated the more frequent the meetings, closer the supervision and control over managers, the more relevant would be the advisory role.…”
Section: Board Meeting Frequencymentioning
confidence: 99%